Efficacy and potential use of vitamin D in the prevention and treatment of uterine fibroids - Martyna Kozłowska; Aleksander Woźniak; Patryk Sydor; Marcel Wartacz; Mateusz Góra; Rafał Kreft; Adrian Krzysztof Hunek; Anna Maria Bigdoń; Maciej Ćwiek; Przemysław Gorczyca (Kazimierz Wielki University, 2023)
Introduction: Uterine fibroids (UFs) are the most common benign gynecological tumors. Pharmacological and/or surgical treatments are frequently required, depending on the woman's desire to preserve fertility. Due to side effects caused by pharmacological and surgical treatments, there is a growing interest in a safe approach for UFs. In recent years, hypovitaminosis D is believed to be a major risk factor in the development of a tumor. Studies proved vitamin D efficacy in inhibiting UFs growth by targeting pathways involved in the regulation of various biological processes, resulting in inhibition of tumor cell division and a significant reduction in its size. Vitamin D seems to be promising, effective, and low-cost method in the management of UFs and their clinical symptoms. Aim of the study: This article reviews the state of knowledge based on available studies. The aim of the study is to present the most important informations about effectiveness and potential usage of vitamin D in prevention and treatment of uterine fibroids. Material and methods: The authors created a paper summarizing review of currently available publications based on databases such as PubMed, Scopus and Google Scholar.